2020
DOI: 10.1101/gad.343038.120
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor EGR2 is the molecular linchpin connecting STAT6 activation to the late, stable epigenomic program of alternative macrophage polarization

Abstract: Macrophages polarize into functionally distinct subtypes while responding to microenvironmental cues. The identity of proximal transcription factors (TFs) downstream from the polarization signals are known, but their activity is typically transient, failing to explain the long-term, stable epigenomic programs developed. Here, we mapped the early and late epigenomic changes of interleukin-4 (IL-4)-induced alternative macrophage polarization. We identified the TF, early growth response 2 (EGR2), bridging the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 54 publications
9
64
0
Order By: Relevance
“…Recently, the synthetic agonist-and antagonist-insensitive (so-called pharmacologically non-responsive) fractions of LXRa and b cistromes were also identified in non-polarized murine immortalized BMDMs further confirming those opinions that the ligand insensitive fraction of lipid sensing nuclear receptor cistromes is general rather than cell type or nuclear receptorspecific phenomenon (86). It has been previously described that IL-4 can enhance the ligand-dependent activity of PPARg in human and murine alternatively polarized macrophages through three different mechanisms including EGR2 transcription factor-dependent activation of its expression, induction of endogenous ligand producing mechanisms, and direct protein-protein interaction with IL-4-activated STAT6 (87)(88)(89)(90). Nevertheless, a significant contradiction can be observed between the PPARg-dependency of alternative macrophage polarization and PPARg ligand-activated gene expression signature.…”
Section: Lipid-sensing Nuclear Receptor-directed Ligand Insensitive Rsupporting
confidence: 79%
See 1 more Smart Citation
“…Recently, the synthetic agonist-and antagonist-insensitive (so-called pharmacologically non-responsive) fractions of LXRa and b cistromes were also identified in non-polarized murine immortalized BMDMs further confirming those opinions that the ligand insensitive fraction of lipid sensing nuclear receptor cistromes is general rather than cell type or nuclear receptorspecific phenomenon (86). It has been previously described that IL-4 can enhance the ligand-dependent activity of PPARg in human and murine alternatively polarized macrophages through three different mechanisms including EGR2 transcription factor-dependent activation of its expression, induction of endogenous ligand producing mechanisms, and direct protein-protein interaction with IL-4-activated STAT6 (87)(88)(89)(90). Nevertheless, a significant contradiction can be observed between the PPARg-dependency of alternative macrophage polarization and PPARg ligand-activated gene expression signature.…”
Section: Lipid-sensing Nuclear Receptor-directed Ligand Insensitive Rsupporting
confidence: 79%
“…It has been previously described that IL-4 can enhance the ligand-dependent activity of PPARγ in human and murine alternatively polarized macrophages through three different mechanisms including EGR2 transcription factor-dependent activation of its expression, induction of endogenous ligand producing mechanisms, and direct protein-protein interaction with IL-4-activated STAT6 ( 87 90 ). Nevertheless, a significant contradiction can be observed between the PPARγ-dependency of alternative macrophage polarization and PPARγ ligand-activated gene expression signature.…”
Section: Lipid-sensing Nuclear Receptor-directed Ligand Insensitive Rmentioning
confidence: 99%
“…EGR2 associates with the NAB2 corepressor 34 and early work in a murine model for macrophage differentiation suggested that EGR2 represses neutrophil-specific genes during monocytic maturation 35 , 36 . However, NAB2 was also identified as an essential co-factor for the recruitment of the mediator subunit INST13 to EGR1/2-bound enhancer elements in human monocyte/MAC 37 and more recent studies in mice have implicated EGR2 in the regulation of transcriptional networks in alternatively activated MAC 38 downstream of STAT6 39 . EGR2 is also required for the upregulation of key factors driving T cell anergy 40 , and associated with genes upregulated during in vitro differentiation of human MO into MAC 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Out of the Early Growth Response (EGR) family members only Egr2 is expressed in unstimulated BMDMs and rapidly induced after IL-4 stimulation (Figure 4D, S4C). Egr2 has also been associated with late IL-4 enhancer activation in a recent study (Daniel et al, 2020). Examination of the Egr2 locus indicates IL-4 induced binding of STAT6 and PPARg to a set of upstream super enhancers that gain H3K27ac and RNA Pol2 signal after IL-4 stimulation (Figure 4E).…”
Section: Resultsmentioning
confidence: 88%
“…In macrophages, IL-4 drives an ‘alternatively activated’ program of gene expression associated with inhibition of inflammatory responses and promotion of wound repair (Gordon and Martinez, 2010). The immediate transcriptional response to IL-4 is mediated by activation of STAT6 (Goenka and Kaplan, 2011; Ostuni et al, 2013), which rapidly induces the expression of direct target genes that include effector proteins such as Arginase 1 ( Arg1 ) and transcription factors like PPARg (Daniel et al, 2018; Huang et al, 1999) and EGR2 (Daniel et al, 2020). However, the extent to which natural genetic variation influences the program of alternative macrophage activation has not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%